Serological evidence of hantavirus infection in apparently healthy people from rural and slum communities in southern Chile - Muñoz-Zanzi, Claudia (2015)
Fil: Muñoz-Zanzi, Claudia. Division of Epidemiology and Community Health, School of Public Health, University of Minnesota; Estados Unidos.